Distribution of Satellite DNA Sequences Isolated from Arctic Char, Salvelinus alpinus , in the Genus Salvelinus - Hartley, S. E.; Davidson, W. S. (Canadian Journal of Fisheries and Aquatic Sciences, 1994)
The distribution of satellite DNA sequences in the genus Salvelinus has been investigated by hybridization of four satellite DNA families isolated from Arctic char, Salvelinus alpinus, to the genomic DNA of S. alpinus, S. fontinalis, S. malma, S. namaycush, S. confluentus, and S. leucomaenis. The distribution of homologous AluI, DraI, and EcoRI satellite sequences suggests a close relationship between S. alpinus, S. malma, and S. confluentus with S. leucomaenis split from all the other species. S. namaycush has a closer relationship to the S. alpinus–malma–confluentus group than does S. fontinalis. The MboI satellite, which has potential as a marker for population differentiation in S. alpinus, has a species distribution suggestive of an ancient salmonid satellite that may have been lost from some species during transposition events.